Building Energy Performance of Complex Forms: Test Simulation of Minimal Surface-Based Form Optimization - Agirbas, Asli (Ecaade-Education & Research Computer Aided Architectural Design Europe, 2020)
Many optimization tools are developed in line with the form-energy relationship to ensure energy efficiency in buildings. However, such studies with complex forms are very limited. Therefore, the MSO-2 model was developed. In this model, on the roof of the conceptual form, minimal surface is used, thus complex forms can be created. In this model, the conceptual form can be optimized (for one day) according to these objectives: increasing daylight in the space with maximum value limitation, reducing radiation on the roof, and enlarging floor surface area of the conceptual form with minimum value limitation. A test simulation was performed with this model. Thus, in order to find the most optimized form in multi-objective optimization, more generations could be produced in a short time and optimized conceptual forms, which were produced, could be tested for energy efficiency.
Keywords: Multi-Objective Optimization; Radiation Analysis; Building Energy Performance; Daylighting Analysis